Making lCT Based Child Society by Collaborative Learning with SLMS: Ideas for Bangladeshi Primary School Leaders - Shanta Akther Sheema (LPPM UNY, 2012)
LMS is a well known teaching method of ICT in the world. As in many other countries, it is not familiar in Bangladesh. However, to make the country a